"Imagine you are auditioning for the Viennese opera": masterclasses and the assessment of operatic habitus. Issue 4 (8th August 2019) - Gvion, Liora
ABSTRACT: Being neither one-to-one classes nor concerts, masterclasses for opera singers are considered locales that provide young singers with an opportunity to perform for a highly esteemed figure in the hopes that the master's feedback will improve their future performances. However, masterclasses can also be looked at as social texts that read through the means of assessing young trainees on the basis of their potential acceptance into the international culture of opera. Intertwining a linguistic perspective as suggested by de Saussere, which distinguishes between "language" and "speech, " with a Bourdieuian perspective that focuses on habitus and cultural capital enables looking at master classes as arenas for assessing young professionals' operatic habitus and pointing to the components which constitute cultural capital either cumulative or innate. As such, masterclasses become institutions that reinforce Western supremacy of the operatic world and limit the access of individuals of non-European origin.